Chloride permeability of concrete mixed with activity recycled powder obtained from C&D waste. (28th February 2019) - Ma, Zhiming; Li, Wei; Wu, Huixia; Cao, Chengwei
Highlights: Replacing cement partially by RP obtained from C&D waste to prepare RPC. Investigating the hydration activity, compound composition and strengths of concrete with various RP contents. Chloride permeability of RPC with and without imposed damage are determined. Abstract: Some studies were developed to investigate the potential of using recycled powder (RP), obtained from the construction and demolition (C&D) wastes, to partially replace the cement in concrete, whereas the chloride permeability of preparing recycled powder concrete (RPC) has not been investigated. This paper shows a comprehensive experiment to study the fundamental characteristics and chloride permeability of RPC. The capillary salt absorption, chloride diffusion and wet-dry cycles tests were carried out on the RPC, respectively, and the chloride permeability with the coupling of freeze-thaw damage was also investigated. The results highlight the addition of RP, with a high fineness and activity, improves the hydration reaction and reduces the concrete's porosity, and the concrete compressive strength slightly increases when the RP replacement ratio is 15%. The addition of RP results in the decrease in the chloride permeability, and the concrete with 30% RP replacement ratio possesses the lowest chloride permeability. Replacing the cement by RP reduces the freeze-thaw resistance of concrete, and the imposed freeze-thaw damage further boosts the chloride permeability of RPC. Particularly, the chloride diffusion coefficient of RPC increases linearly with the decreasing of relative dynamic elastic modulus. Basing on the testing results of fundamental characteristics and chloride permeability, the suggested RP replacement ratio in concrete should be below 30%.